Analisis Faktor-Faktor yang Mempengaruhi Kinerja Layanan Karyawan dan Hasil Layanan Pelanggan pada Industri Restoran Waralaba di Kota Manado - Laoh, Sinjo James (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
The purpose of this research was to explore how the relationship on service performance based on the individual level such as conscientiousness, neuroticism, extraversion, and agreeableness, and on the restaurant level such as service climate, employee involvement, service training and performance incentives on 85 employees, 12 managers, and 840 customers in 6 restaurant chains in Manado city. Factors that exist on individual and on the restaurant level have a significant relationship to employee service performance: on individual, factors such as conscientiousness and extraversion as evidence on within-restaurant variance and service climate as shown in between store variance, and on restaurant level, aggregate employee performance as shown on between store variance of customer's satisfaction and loyalty.